2021
DOI: 10.3390/ijms22179136
|View full text |Cite
|
Sign up to set email alerts
|

Role of the Myokine Irisin on Bone Homeostasis: Review of the Current Evidence

Abstract: Bone is a highly dynamic tissue that is constantly adapting to micro-changes to facilitate movement. When the balance between bone building and resorption shifts more towards bone resorption, the result is reduced bone density and mineralization, as seen in osteoporosis or osteopenia. Current treatment strategies aimed to improve bone homeostasis and turnover are lacking in efficacy, resulting in the search for new preventative and nutraceutical treatment options. The myokine irisin, since its discovery in 201… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 95 publications
(206 reference statements)
1
17
0
Order By: Relevance
“…The interaction between irisin and osteoactivin may be through their role in the process of osteoblast differentiation as both exert their function by binding to integrin receptors (58,62). Furthermore, it has been reported that treatment with irisin induces osteoblast differentiation, which in turn resulted in an increase in OPG levels (16,63). The association observed through the current study between the levels of irisin and OPG agrees with these findings.…”
Section: Discussionsupporting
confidence: 89%
“…The interaction between irisin and osteoactivin may be through their role in the process of osteoblast differentiation as both exert their function by binding to integrin receptors (58,62). Furthermore, it has been reported that treatment with irisin induces osteoblast differentiation, which in turn resulted in an increase in OPG levels (16,63). The association observed through the current study between the levels of irisin and OPG agrees with these findings.…”
Section: Discussionsupporting
confidence: 89%
“…As for the mechanism, irisin may increase the proliferation, differentiation, and mineralization of osteoblasts through activating the Wnt/β-catenin pathway and p38 mitogen-activated protein kinase and extracellular signal-regulated kinase (p38/ERK MAPK) signaling pathway. Increased expression of RUNX2, which is an important osteogenic marker, and downstream stimulation of ALP and OC were found in the the Wnt/β-catenin and p38/ERK MAPK signaling pathway [31]. Moreover, irisin could reduce osteoclastogenesis through decreasing RANKL-induced osteoclast differentiation and NFAT1c signaling pathway [32].…”
Section: Discussionmentioning
confidence: 98%
“…Previous studies demonstrated that irisin was a stronger determinant of bone mineral status ( 32 ), increasing bone formation and decreasing bone resorption, leading to reduced risk of osteoporosis. Irisin had been shown to play an important role in promoting osteoblastogenesis and reducing osteoclastogenesis ( 33 ). Therefore, we speculate the beneficial effects of irisin on bone protection in postmenopausal women with sarcopenia.…”
Section: Discussionmentioning
confidence: 99%